Constructivism and Contextual Based Learning in Improving Indonesian Language Learning Outcomes in Five Grade First Semester at State Elementary School 44 Oku Using Online Learning Techniques In The Middle of The Covid 19 Pandemic - Sulistiyono, Edy; Missriani; Fitriani, Yessi (Jurnal Pendidikan Tambusai, 2021)
This study aims to determine the success of implementing constructivism-based and contextual learning systems in Indonesian language learning, in particular, the five-grade first semester at SD Negeri 44 OKU with on-line learning techniques in the midst of the Covid-19 pandemic. This study uses qualitative research methods. The data collection techniques used were participant observation, structured interviews, and documentation. The results showed several recommendations for distance learning designs by viewing teaching as a process of interaction between learning actors. Interactions that are mediated by this technology need to be carefully designed and implemented based on the needs of students. Apart from what has been shared here, the spaces for innovation are still very wide open in the design and implementation of distance learning, with learning spaces to continuously improve teaching. The vast space for innovation and learning is what frees educators to continue to observe, ask, try, find, and reflect on what forms of distance learning are most appropriate to the context of their students.